2021
DOI: 10.1002/ece3.7667
|View full text |Cite
|
Sign up to set email alerts
|

Who’s for dinner? Bird prey diversity and choice in the great evening bat, Ia io

Abstract: The mysterious predator–prey interaction between bats and nocturnally migrating birds is a very rare and incredible process in natural ecosystems. So far only three avivorous bat species, including two noctule bats ( Nyctalus lasiopterus and Nyctalus aviator ) and the great evening bat ( Ia io ), are known to regularly prey on songbirds during nocturnal avian migration. The information related to the diversity and the characteristics of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 43 publications
(74 reference statements)
0
33
0
Order By: Relevance
“…This cave is mainly a colony of I. io males. In the winter, individual bats either hibernate in this cave or migrate farther south to overwinter elsewhere ( 24 ). Our previous studies had shown that individual bats within this population mostly prey on insects in the summer (June to August) and on birds in the autumn (September to November) ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This cave is mainly a colony of I. io males. In the winter, individual bats either hibernate in this cave or migrate farther south to overwinter elsewhere ( 24 ). Our previous studies had shown that individual bats within this population mostly prey on insects in the summer (June to August) and on birds in the autumn (September to November) ( 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the winter, individual bats either hibernate in this cave or migrate farther south to overwinter elsewhere ( 24 ). Our previous studies had shown that individual bats within this population mostly prey on insects in the summer (June to August) and on birds in the autumn (September to November) ( 24 ). Bats were captured using a mist net at the entrance to the cave after they returned from foraging (between 20:00 and 07:00).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations